Single-port versus multi-port robotic sacrocervicopexy: Establishment of a learning curve and short-term outcomes. (August 2019) - Lauterbach, Roy; Mustafa-Mikhail, Susana; Matanes, Emad; Amit, Amnon; Wiener, Zeev; Lowenstein, Lior
Abstract: Objectives: The purpose of this study was to compare the learning curves, surgical outcomes and complications of multi-port access robotic-assisted laparoscopic sacrocervicopexy (MP-RSC) to single-port robotic access (SP-RSC) for vaginal apex prolapse. Methods: A retrospective study of the first 52 MP-RSC procedures compared with the first 52 SP-RSC procedures performed at one medical center. Primary outcomes were intraoperative bleeding, operative time, and hospitalization. Secondary outcomes were surgical complications. Results: There was a statistically significant difference in mean operative times between the MP-RSC and SP-RSC procedures: 206.5 ± 39.4 and 187.8 ± 46.2, respectively, P = 0.028. The mean estimated intraoperative blood loss was 35 [20–87.5] ml and 20 [10–47.5] ml, respectively, P = 0.008. Respective mean operative times decreased from the first 15 to the subsequent 15 cases: in the MP-RSC group from 224.2 ± 43.2 to 198.4 ± 36.3 min, P = 0.088, and in the SP-RSC group from 222.4 ± 53.1 to 161.3 ± 28.2 min, P < 0.001. The subsequent 22 cases showed different trends. Hospitalization (days) and level of pain at 24 h postoperative, according to a 1–10 point visual analogue scale, did not differ. Adverse events were rare in both groups. Conclusions: MP-RSC and SP-RSC are feasible and the short term outcomes and learning curves for both procedures are comparable.